2020
DOI: 10.1016/j.ymthe.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Theta Modulates PCMT1 through hnRNPL to Regulate FOXP3 Stability in Regulatory T Cells

Abstract: T cell receptor signaling, together with cytokine-induced signals, can differentially regulate RNA processing to influence T helper versus regulatory T cell fate. Protein kinase C family members have been shown to function in alternative splicing and RNA processing in various cell types. T cell-specific protein kinase C theta, a molecular regulator of T cell receptor downstream signaling, has been shown to phosphorylate splicing factors and affect post-transcriptional control of T cell gene expression. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Our own studies identified RNA processing factors, including hnRNP A1 and hnRNP L, as Akt targets during T H cell differentiation [15] . A recent study examined the role of AS and RNA processing in Treg induction and stability [49] . This study showed that inhibition of PKCθ during in vitro Treg differentiation altered AS patterns by affecting the activity of the RNA processing factor hnRNP L and the methyltransferase PCMT1, leading to greater stability of Treg [49] .…”
Section: Akt and The Regulation Of Asmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own studies identified RNA processing factors, including hnRNP A1 and hnRNP L, as Akt targets during T H cell differentiation [15] . A recent study examined the role of AS and RNA processing in Treg induction and stability [49] . This study showed that inhibition of PKCθ during in vitro Treg differentiation altered AS patterns by affecting the activity of the RNA processing factor hnRNP L and the methyltransferase PCMT1, leading to greater stability of Treg [49] .…”
Section: Akt and The Regulation Of Asmentioning
confidence: 99%
“…A recent study examined the role of AS and RNA processing in Treg induction and stability [49] . This study showed that inhibition of PKCθ during in vitro Treg differentiation altered AS patterns by affecting the activity of the RNA processing factor hnRNP L and the methyltransferase PCMT1, leading to greater stability of Treg [49] . While this study did not directly examine the role of Akt, the authors proposed that it could be playing a role in controlling PCMT1 function, and further studies are needed to confirm this speculation.…”
Section: Akt and The Regulation Of Asmentioning
confidence: 99%
See 1 more Smart Citation
“…The main functions of PCMT1 are to initiate the repair of damaged proteins by catalyzing methyl esterification of L-isoaspartyl and D-aspartyl residues produced by spontaneous isomerization and racemization of L-aspartyl and L-asparaginyl residues in aging peptides and proteins. Previous studies have shown that strong PCMT1 expression is not only a predictive marker for poor prognosis of surgically removed lung adenocarcinoma but also an unfavorable prognostic biomarker for bladder cancer [ 12 14 ]. It participates in cell migration and invasion by regulating epithelial-mesenchymal transition-related genes and acts as an oncogene in bladder cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…39,42 Additionally, PTDMs constructed from a hydrophobic monomer featuring methyl and phenyl substituents (MePh) and a cationic monomer containing two guanidine groups (dG) have demonstrated robust delivery of several functional proteins, including antibodies and enzymes. 29,[42][43][44][45][46] Maintaining a 2 : 1 ratio of MePh to dG, five carriers were synthesized with DPs of 15-120 (6-46 kDa in size). This series of block copolymers was used here to deliver EGFP, IgG, and Cre recombinase to elucidate the impact of molecular weight on both internalization and protein activity.…”
Section: Introductionmentioning
confidence: 99%